Mechanisms Used by Probiotics to Confer Pathogen Resistance to Teleost Fish - Simón, Rocío; Docando, Félix; Nuñez-Ortiz, Noelia; Tafalla, Carolina; Díaz-Rosales, Patricia (Frontiers in Immunology, 2021)
Probiotics have been defined as live microorganisms that when administered in adequate amounts confer health benefits to the host. The use of probiotics in aquaculture seems as an attractive bio-friendly method to decrease the impact of infectious diseases, but is still not an extended practice. Although many studies have investigated the systemic and mucosal immunological effects of probiotics, not all of them have established whether they were actually capable of increasing resistance to different types of pathogens, being this the outmost desired goal. In this sense, in the current paper, we have summarized those experiments in which probiotics were shown to provide increased resistance against bacterial, viral or parasitic pathogens. Additionally, we have reviewed what is known for fish probiotics regarding the mechanisms through which they exert positive effects on pathogen resistance, including direct actions on the pathogen, as well as positive effects on the host.